Current approach for urinary system stone disease in pregnant women - İLBEY, YUSUF ÖZLEM; Celik, Orcun; Turk, Hakan; Cakmak, Ozgur; Ekin, Rahmi Gokhan; Keskin, Mehmet Zeynel; Yildiz, Guner; Ilbey, YUSUF ÖZLEM (My University, 2015)
Urinary system stones can be classified according to size, location, X-ray characteristics, aetiology of formation, composition, and risk of recurrence. Especially urolithiasis during pregnancy is a diagnostic and therapeutic challenge. In most cases, it becomes symptomatic in the second or third trimester. Diagnostic options in pregnant women are limited due to the possible teratogenic, carcinogenic, and mutagenic risk of foetal radiation exposure. Clinical management of a pregnant urolithiasis patient is complex and demands close collaboration between patient, obstetrician and urologist. We would like to review current diagnosis and treatment modalities of stone disease of pregnant woman.